2011
DOI: 10.1007/s00436-011-2267-x
|View full text |Cite
|
Sign up to set email alerts
|

Antischistosomal activity of ginger (Zingiber officinale) against Schistosoma mansoni harbored in C57 mice

Abstract: The repeated chemotherapy of schistosomiasis has resulted in the emergence of drug-resistant schistosome strains. The development of such resistance has drawn the attention of many authors to alternative drugs. Many medicinal plants were studied to investigate their antischistosomal potency. The present work aimed to evaluate antischistosomal activity of crude aqueous extract of ginger against Schistosoma mansoni. Sixteen mice of C57 strain were exposed to 100 ± 10 cercariae per mouse by the tail immersion met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 39 publications
(43 reference statements)
9
55
0
1
Order By: Relevance
“…In the present work, the total worm burden was reduced from 45 to 57%, which is more or less similar to that found by Mostafa et al [47]. However, the reduction of the total worm burden is 31-39% after treatment with arachidonic acid [18] which is lower than that of the present study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present work, the total worm burden was reduced from 45 to 57%, which is more or less similar to that found by Mostafa et al [47]. However, the reduction of the total worm burden is 31-39% after treatment with arachidonic acid [18] which is lower than that of the present study.…”
Section: Discussionsupporting
confidence: 88%
“…However, the reduction of the total worm burden is 31-39% after treatment with arachidonic acid [18] which is lower than that of the present study. While the percentage of egg reduction was 56-74% in the liver which is much more if compared to egg reduction in that treated with ginger [47]. A higher number of males were recovered from mice if compared to female worms obtained from the same mice (Table 1).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results of the present study showed that the susceptibility of male and female worms to venom varied, with male worms being more susceptible than females were. In this regard, male S. mansoni worms were also more susceptible than females were to praziquantel, ginger extract, diamines, and amino alcohols and to treatment with certain essential oils (35) (36) (37) (38) (39) . However, there was no differential sensitivity to piplartine between male and female worms in vitro (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning Z. officinale, results are in agreement with those of Sanderson et al (2002) who reported that neither oral nor subcutaneous administration of 150 mg/ kg of ethyl acetate extract of ginger produced any significant reduction in S. mansoni worm numbers compared with untreated controls. Conversely, Mostafa et al (2011) reported that worm burden and the egg density in liver and faeces of mice treated with ginger were fewer than in non-treated ones. Table 4.…”
Section: Safety and In Vivo Efficacy Against S Mansonimentioning
confidence: 98%